AN ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACT IN THE MOVIE MALEFICENT - Pratama, Sang Ade Satria; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2021)
Language is said to be something that is obligatory in communicating for humans. Without a proper communication, relationship between human beings would never run smoothly. The area of this phenomenon is commonly called pragmatics and one major theory that has been effective for analysis is Speech Act Theory. This study is aimed to answer the research problems, which comprise: (1) to find out types of directive illocutionary act are used by the main characters in the Maleficent movie and (2) to identify function of directive illocutionary act used by the main characters in the Maleficent movie. The data in this research was the Maleficent movie and analyzed by applying illocutionary acts theory proposed by Searle (1979) and Leech (1983) theory of illocutionary functions to analyze the goal. This study used descriptive qualitative method to analyze the data and quantitative method to find out about the frequency of type that implied in the Maleficent movie. The finding shows that there are four types of directive illocutionary act which used by the main characters in the Maleficent movie, they are: asking act (50%), commanding act (30%), requiring act (10%) and telling act (10%)